2020
DOI: 10.3390/tropicalmed5040176
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility and Molecular Characterization of Uropathogenic Escherichia coli Associated with Community-Acquired Urinary Tract Infections in Urban and Rural Settings in South Africa

Abstract: We investigated the phenotypic and genotypic antibiotic resistance, and clonality of uropathogenic Escherichia coli (UPEC) implicated in community-acquired urinary tract infections (CA-UTIs) in KwaZulu-Natal, South Africa. Mid-stream urine samples (n = 143) were cultured on selective media. Isolates were identified using the API 20E kit and their susceptibility to 17 antibiotics tested using the disk diffusion method. Extended-spectrum β-lactamases (ESBLs) were detected using ROSCO kits. Polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
2
11
2
Order By: Relevance
“…coli is recognized as the predominant uropathogen in UTIs, accounting for 75%-95% of all UTIs all over the world. 9 Similarly, in the present study, we revealed that E. coli is the major pathogen of COUTIs in China, accounting for about three quarters of all the causative pathogens.…”
Section: Discussionsupporting
confidence: 76%
“…coli is recognized as the predominant uropathogen in UTIs, accounting for 75%-95% of all UTIs all over the world. 9 Similarly, in the present study, we revealed that E. coli is the major pathogen of COUTIs in China, accounting for about three quarters of all the causative pathogens.…”
Section: Discussionsupporting
confidence: 76%
“…The common pathogens identified in this study are in general consistent with the findings of other recently published South African studies. 6 , 14 , 15 The relatively high number of E. faecalis infections (2016: 17.4%) in this study is similar to that seen in the pooled 2015–2019 data for four Gauteng tertiary centres (including CMJAH) but higher than that reported for 2011–2016 in KZN (4.2%). The second most common pathogen in KZN was K. pneumoniae .…”
Section: Discussionsupporting
confidence: 85%
“…HPV is the leading cause of cervical cancer, which is the leading cause of cancer death in women in Africa. It is therefore a real public health problem, especially because some of the circulating genotypes are not covered by existing and available vaccines [16][17][18]. Pathogens such as NG, MG and CT would promote HPV infection which in turn could persist and induce precancerous lesions or cervical intraepithelial neoplasia type 1, 2 or 3 (CIN1, CIN2 and CIN3), which may regress or progress to cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction was performed at CERBA/LABIOGENE using the DNA-Sorb-A kit from SACACE Biotechnologies ® (Reference K-1-1/A/100, Lot 23B16A155), following the protocol provided by the manufacturer. For the molecular diagnosis of HPV, the "HPV Genotypes 14 Real-TM Quant" real-time amplification kit from SACACE Biotechnologies ® (Reference V67-100FRT, Lot 26 G17K414) detecting 14 high-risk HPV genotypes was used (HPV 16,18,31,33,35,39,45,51,52,56,58,59,66.68). PCR was performed using the SaCycler-96 real-time PCR device in version 7.3 of SACACE Biotechnologies ® .…”
Section: Molecular Characterization 241 Dna Extractionmentioning
confidence: 99%